2011
DOI: 10.5539/ijb.v3n2p75
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Activity of Methanol Extracts of Rubus idaeus L.

Abstract: The purpose of this article is to evaluate the diuretic potential of Rubus idaeus L. fruits. By measuring the urine volume of experimental animals, we find that methanol extract of Rubus idaeus L. fruits significantly increased the urine volume of experimental animals suggesting its diuretic effect. This is the first formal report on the diuretic activity of Rubus idaeus L. fruits. Moreover, four fractions isolated from the methanol extract were further studied and the results showed that ethyl acetate fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Ying Zhang et al .,[ 17 ] compared diuretic activity of Rubusidaeus L. extracts with hydrochlorothiazide (synthetic diuretic) in rat. They showed that hydrochlorothiazide had a higher inhibitory effect on electrolyte (Na + , K + and Cl - ) in rats than the extracts, nevertheless their abilities for inhibiting the UV were similar with our results in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Ying Zhang et al .,[ 17 ] compared diuretic activity of Rubusidaeus L. extracts with hydrochlorothiazide (synthetic diuretic) in rat. They showed that hydrochlorothiazide had a higher inhibitory effect on electrolyte (Na + , K + and Cl - ) in rats than the extracts, nevertheless their abilities for inhibiting the UV were similar with our results in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Dichloromethane is a common solvent used in volatile analysis. Methanol was selected in order to evaluate this solvent as a new option for aroma studies; it was previously used by Zhang and others (2011), Hannus and others (2006), and Sule and others (2005). By means of chromatograms comparison between dichloromethane and methanol extracts, methanol extract had a major quantity of volatile compounds.…”
Section: Methodsmentioning
confidence: 99%